Understanding reforms post-1991 India - Tendulkar, Suresh D.; Bhavani, T. A. (New Delhi ; Oxford : Oxford University Press, 2012)
The book traces the remarkable transformation of India from a slow growing economy to one of the fastest growing in the world. Discussing events that led to a crisis situation and the consequent initiation of reforms, it describes how growth was sustained in a low-income economy with large diversities.
Previous ed.: 2007.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: India -- Economic policy -- 1991-